Effect of interpersonal addictions of school of health students to substance use cases - Bilge, Ayşegül; Embel, Nadide; Kaya, Fatma Gül (Journal of Dependence, 2014)
Objective: Research has been done for the purpose of determining the effect of interpersonal addictions of school of health students to substance use cases. Method: 376 students who are registered in a school of health’s departments of nursing, midwife, feeding and dietetic in 2012 - 2013 school years, formed the sample group of research planned in sectional type. To make the research, written approval from the institution and spoken approval from students were gotten. A poll form which includes socio-demographic characteristics and Interpersonal Addiction Criterion were used as data collection means. Results: 7.9 percent of participants were men and 14.8 percent of participants were students of nursing department, average age of participants was 21.04 ±1.56. Women compared to men, feel more emotional confidence and less social self-confidence. It was determined that the ones who say ‘’ Yes ‘’ to the question “Have you ever used any substance?” feel less lack of social self-confidence, compared to the ones who say ‘’ No ‘’. Most of the students think that there is no connection between substance use and communication manner. It was determined that lack of social self-confidence is felt minimum among students who study in Departments of Feeding and Dietetic and a statistical meaningful difference has been established. Conclusion: According to the results of the research students are interpersonal dependent and autonomic so they have the risk of making substance use decisions. For this reason it is suggested that especially university students who will take charge in health discipline, should be evaluated and supported by dependence units.